Кримінально-правова охорона об’єктів культурної спадщини від сучасних загроз тероризму - Юртаєва, К. В.; Yurtayeva, K. V.; ORCID: http://orcid.org/0000-0002-6096-2020; ResearcherID: D-1818-2016 (Вісник Кримінологічної асоціації України. - 2015. - № 3 (11). - С. 125-136., 2015)
У статті розглянуто особливості кваліфікації тероризму, пов’язаного з незаконним поводженням з об’єктами культурної спадщини. Визначено особливості норм, що встановлюють кримінальну відповідальність за незаконне поводження з об’єктами культурної спадщини у мирний час та в умовах збройних конфліктів. Виявлено вади у встановленні кримінальної відповідальності щодо руйнування об’єктів культурної спадщини в умовах збройного конфлікту, запропоновано шляхи їх усунення.

Features of terrorism qualification associated with unlawful handling with the objects of cultural heritage are studied in the article. The key to overcome terrorism in Ukraine is a combination of studying the issue of modern threats of terrorism on a scientific level, circumspect preventive criminalization and forming effective organizational and legal system of counteracting this dangerous social phenomenon. Forms and methods used by radical groups around the world to maintain their existence and attract new members have undergone prominent changes in recent years. One of the modern manifestations of terrorism is a threat of terrorist attacks on the objects of cultural heritage and the use of illicit trafficking of cultural property to finance organized terrorist groups. The institution of criminal and legal protection of cultural property can be divided into two groups of norms: the first is related to the regulation of the protection of cultural property during armed conflicts; the second is associated with the protection of cultural property in peacetime. In domestic legislation the liability for illegal handling with cultural property during armed conflicts is enshrined in the Art. 438 of the Criminal Code of Ukraine. The analysis of the disposition of this Article reveals serious shortcomings in establishing criminal liability concerning the destruction of the objects of cultural heritage within armed conflicts. To eliminate them we believe the necessary thing is the accession and ratification of the Second Protocol to the Convention for the Protection of Cultural Property in the Event of Armed Conflict dated from 1954 as soon as possible. The second group of crimes, associated to causing damage to the objects of cultural heritage in peacetime, include crimes under the Articles 178, 179, 193, 201, 298 of the Criminal Code of Ukraine. Analysis of international legal practice proves the fact that illegal handling of terrorists with the objects of cultural heritage may have the form of: 1) the intentional destruction of the objects of cultural heritage for terrorizing people and governments of different countries; 2) illegal trade in cultural artefacts, which provides funding for terrorist groups. The first type of illegal handling with the objects of cultural heritage must be qualified for cumulation of the Articles 258 and 298 of the Criminal Code of Ukraine. In the case of the destruction of the most valuable objects of cultural heritage, in particular, referred to the Unesco World Heritage List, committed acts should be qualified according to p. 2 of the Art. 258 of the Criminal Code of Ukraine as a terrorist act that led to serious consequences. The commission of socially dangerous acts related to illegal acquisition or unlawful movement across the customs border of Ukraine of the objects of cultural heritage aiming at financial or material support of terrorism should be qualified with the presence of appropriate attributes by cumulation of the Articles 185–187, 189–191, 193, 201, 297, 432, 433 or 438 and the corresponding paragraph of the Article 258-5 of the Criminal Code of Ukraine “Financing terrorism”.

В статье рассмотрены особенности квалификации терроризма, связанного с незаконным обращением с объектами культурного наследия. Определены особенности норм, которые устанавливают уголовную ответственность за незаконное обращение с объектами культурного наследия в мирное время и в условиях вооруженных конфликтов. Выявлены недостатки в установлении уголовной ответственности за разрушение объектов культурного наследия в условиях вооруженного конфликта, предложены пути их устранения.
Юртаєва, К. В. Кримінально-правова охорона об’єктів культурної спадщини від сучасних загроз тероризму // Вісник Кримінологічної асоціації України. - 2015. - № 3 (11). - С. 125-136.
Юртаєва К. В. "Кримінально-правова охорона об’єктів культурної спадщини від сучасних загроз тероризму." Вісник Кримінологічної асоціації України 3 (2015): 125-136.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; тероризм; об’єкти культурної спадщини; збройний конфлікт; кримінально-правова політика; terrorism; object of cultural heritage; armed conflict; criminal and legal policy; терроризм; объект культурного наследия; вооруженный конфликт; уголовно-правовая политика